“Double Prosthesis Implantation”: Biometry and Refractive Outcomes in Combined Intraocular Lens and Artificial Iris Surgery - Mayer C (Dove Medical Press, 2021)
Christian Mayer, Ramin Khoramnia Department of Ophthalmology, University Hospital Heidelberg, University of Heidelberg, Heidelberg, GermanyCorrespondence: Christian MayerDepartment of Ophthalmology, University Hospital Heidelberg, University of Heidelberg, Im Neuenheimer Feld, 400, Heidelberg, 69120, GermanyEmail christian.mayer@med.uni-heidelberg.dePurpose: To assess the biometry and postoperative refraction in iris repair using ArtificialIris in combination with an intraocular lens (IOL).Setting: Department of Ophthalmology, University Hospital Heidelberg, University of Heidelberg, Germany.Design: Retrospective observational study.Methods: We included 44 aniridic and aphakic eyes for IOL implantation in combination with iris prosthesis reconstruction. The iris prostheses were either sutured into the ciliary sulcus and fixed by transscleral suturing or were implanted together with a capsular tension ring and the IOL in the capsular bag. The primary outcomes measured were pre- and postoperative best corrected visual acuity (CDVA), objective and subjective refraction, anterior chamber depth and optical biometry comparing common IOL formulae.Results: Reasons for surgery were trauma (39 eyes), iatrogenic causes (1 eye), aniridic state after severe iritis (2 eyes) or iris tumor (2 eyes). Monocular CDVA improved significantly (p< 0.0001) from median 0.55 logMAR (0.0 to 1.98) to 0.16 logMAR (− 0.08 to 2.0). There were no significant differences between the postoperative target refraction calculated by the formulae “Haigis”, “Hoffer-Q”, “SRK/T” and “Holladay 1” (p=0.68). The absolute deviation from target refraction did not differ significantly between the formulae (p=0.87). Median target refraction was − 0.42 D (− 4.0 to 1.68). Postoperatively median spherical equivalent was 0.00 D (− 5.38 to 2.38). Median absolute deviation from target refraction after 5 months of follow-up was 0.98 D (0.06 to 5.17).Conclusion: Postoperative refraction using common techniques and using preoperative biometry revealed a well predictable postoperative refraction. There is no correction factor needed.Keywords: aniridia, aphakia, artificial iris, secondary IOL implantation